Respiratory outcomes with the use of a lower custom fit genioglossal‐effecting oral appliance - Dena P. Garner; Jensine Lamira (Wiley, 2020)
Abstract Objective Sleep apnea research cites that an oral appliance, which places the mandible in a more forward position and the genioglossus (tongue muscle) on the floor of the mouth, improves aspects of the pharyngeal opening. Exercise science research has cited improvements in airway dynamics and physiological variables with oral appliance use during exercise. Thus, the purpose of this study was to design an oral appliance that would act on the genioglossus and determine if there were effects on respiratory parameters while exercising. Materials and methods Seventeen healthy subjects ages 18-43 participated in this study. Prior to the exercise protocol, the order of the oral applicance (OA) or no oral appliance (no OA) condition was randomly assigned to subjects, with subjects completing both conditions. Respiratory parameters (respiratory rate, ventilation, oxygen, and carbon dioxide) were measured between conditions while subjects ran for 10 min at steady state. Results The results demonstrated that both respiratory rate (25.97 BPM, OA and 28.35 BPM, no OA) and ventilation (47.66 l/min, OA and 50.34 l/min, No OA) were significantly lowered (p < .01) in the OA condition. There were no differences in carbon dioxide (1.89 l/min, no OA and 1.88 l/min, OA) or oxygen outcomes (2.17 l/min, no OA and 2.17 l/min OA). Discussion The outcomes from this study suggest that the design of the oral appliance elicits an effect on the genioglossus, thereby resulting in lowered respiratory rate and ventilation with no negative effects on oxygen uptake during exercise.